When Two Worlds Collide: Unveiling Ethical Challenges in Early Capitalist and Contemporary Societies Through the Lenses of Marius Bercea's Universe - Blehuiu, Alina Elena (Business ethics quarterly, 2025)
When Two Worlds Collide: Unveiling Ethical Challenges in Early Capitalist and Contemporary Societies Through the Lenses of Marius Bercea's Universe - Volume 35 Issue 4